Effect of temperature on systems for the reinforcement of concrete - Aguiar, J. L. Barroso de (2007)
This paper presents an experimental work using prismatic specimens of hydraulic mortar reinforced on the exterior with steel or CFRP plates. The adhesive used was an epoxy. Two series of tests were made. In the first one, the specimens were exposed seven days to temperatures between 20 ºC and 250 ºC, after which they were subjected to flexure tests made at 20 ºC. In the second series, the specimens were exposed 24 hours to temperatures between 20 ºC and 60 ºC. The exposure to different temperatures was maintained during the flexure tests. In the first series, the efficiency of the reinforcements decreases significantly above 50 ºC. In the second series, the significant decrease of the flexure resistance occurred above 40 ºC. The simultaneous action of temperature and load leads to a lower thermal resistance than the separate action.